2020
DOI: 10.2519/jospt.2020.9753
|View full text |Cite
|
Sign up to set email alerts
|

Workload a-WEAR-ness: Monitoring Workload in Team Sports With Wearable Technology. A Scoping Review

Abstract: Objectives To (1) identify the wearable devices and associated metrics used to monitor workload and assess injury risk, (2) describe the situations in which workload was monitored using wearable technology (including sports, purpose of the analysis, location and duration of monitoring, and athlete characteristics), and (3) evaluate the quality of evidence that workload monitoring can inform injury prevention. Design Scoping review. Literature Search We searched the CINAHL, Cochrane Central Register of Controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 84 publications
3
45
0
1
Order By: Relevance
“…These findings are consistent with previous studies that identified an increased risk of injury was associated with both low chronic workloads and high acute relative to chronic workloads (Hulin et al, 2016a,b;Colby et al, 2017;Stares et al, 2018;Bowen et al, 2020). Several review articles have summarized other studies that also demonstrated an association between high ACWR and injury (Drew and Finch, 2016;Jones et al, 2017;Eckard et al, 2018;Benson et al, 2020a;Griffin et al, 2020). It should be noted that in most cases, the original studies on the workload-injury relationship investigated many combinations of workload metrics and methods for accumulating workload, resulting in the identification of multiple significant associations (Benson et al, 2020a).…”
Section: Workload and Injurysupporting
confidence: 91%
See 2 more Smart Citations
“…These findings are consistent with previous studies that identified an increased risk of injury was associated with both low chronic workloads and high acute relative to chronic workloads (Hulin et al, 2016a,b;Colby et al, 2017;Stares et al, 2018;Bowen et al, 2020). Several review articles have summarized other studies that also demonstrated an association between high ACWR and injury (Drew and Finch, 2016;Jones et al, 2017;Eckard et al, 2018;Benson et al, 2020a;Griffin et al, 2020). It should be noted that in most cases, the original studies on the workload-injury relationship investigated many combinations of workload metrics and methods for accumulating workload, resulting in the identification of multiple significant associations (Benson et al, 2020a).…”
Section: Workload and Injurysupporting
confidence: 91%
“…Several review articles have summarized other studies that also demonstrated an association between high ACWR and injury (Drew and Finch, 2016;Jones et al, 2017;Eckard et al, 2018;Benson et al, 2020a;Griffin et al, 2020). It should be noted that in most cases, the original studies on the workload-injury relationship investigated many combinations of workload metrics and methods for accumulating workload, resulting in the identification of multiple significant associations (Benson et al, 2020a). In contrast to the results of this study, significant associations between workload and injury have also been reported when the chronic workload is high (Colby et al, 2014(Colby et al, , 2018Bowen et al, 2017;Malone et al, 2017;Esmaeili et al, 2018;Jaspers et al, 2018), and embedded in the studies that investigated many combinations of workload and accumulation methods are reports of no association between ACWR and injury (Impellizzeri et al, 2020c).…”
Section: Workload and Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the imprecision of GPS units, they are widely used to monitor the movement of players [ 29 ], while heart rate monitors inform the coaches about levels of exertion [ 18 ] when players are in play. This allows coaches to monitor and influence decisions, such as whether to take a player out to prevent extreme fatigue or injuries when they are performing near maximal exertion.…”
Section: Introductionmentioning
confidence: 99%
“…The increased ability to collect EB data is having a large impact in the field of sports medicine when it comes to monitoring and forecasting workload and cardiovascular health and assessment of injury risk of athletes on various team sports around the world. However, wearable technology is still limited in terms of injury prediction due to different injury definitions and reported workload metrics, poor study quality, and the lack of accurate and multivariate probabilistic models due to an incomplete understanding of the determinants of an injury [10][11][12].…”
Section: Introductionmentioning
confidence: 99%